The Return of Institutions. On the Latest Change in the Research on Social and Economic Development - Szymanowski, Rafał (Wydawnictwo Naukowe WNPiD UAM, 2015)
The paper describes the latest change in the research on social and economic development of states. This change is characterized mainly by a strong emphasis put on the role of institutions as key instruments of reducing the development gap between countries. It is argued that in the years after 1989 institutions have disappeared from mainstream academia and major intellectual debates because of: (1) the widespread belief in global convergence of capitalism and (2) the modernization theory which prevailed in the social science in the 1990s. The article indicates that institutions were once again brought into focus as a result of (1) a wider debate about the institutional sources of growth and development sparked by Acemoglu and Robinson’s Why Nations Fail, (2) the beginning of the global economic crisis of 2008 triggered by the fall of American investment bank Lehman Brothers (3) diversified consequences of the economic crisis seen all over Europe and the USA which illustrate (4) the institutional varieties of capitalism.
Keywords: institutions; new institutionalism; social and economic development; development gap; Varieties of Capitalism (VoC)